Peningkatan Motivasi Belajar Peserta Didik Melalui Modul Ajar Digital pada Pembelajaran Matematika Kelas IV SD - Salwa, Elfina Nazhifah; Sukma, Elfia; Kharisma, Inggria (Indo-MathEdu Intellectuals Journal, 2026)
Low learning motivation in Mathematics is a persistent challenge in elementary schools, particularly those with limited digital infrastructure. This study aims to describe how digital teaching modules improve the learning motivation of fourth-grade students at SDN 08 Talamau, Pasaman Barat. Using a qualitative descriptive approach with a case study design, data were collected through observation, interviews and documentation. Data analysis followed the Miles and Huberman interactive model, with validity ensured through source and technique triangulation. Findings indicate that prior to the intervention, learning was teacher-centered, constrained by limited teacher training since the COVID-19, scarce digital facilities, and recurring power outages. Following the contextual implementation of digital teaching modules, notable improvements were observed across three motivational indicators: attention became more sustained, interest increased as students spontaneously raised questions, and active participation grew through discussion and voluntary engagement. These findings demonstrate that context-sensitive digital teaching modules can serve as an effective strategy to strengthen Mathematics learning motivation in resource-limited elementary schools. This study is limited to a single school with a small sample, restricting generalizability. Future research should employ a mixed-method approach across multiple schools for more comprehensive evidence.